Lactic Acid and Its use in Food Industries) - Arief Budhiono (Balai Besar Industri Agro, 1988)
Lactic acid is an organic acid which is naturally found in the fermented products such as yoghurt, cheese, pickle, beer, wine and meat products. The properties, productions, and use of the lactic acid in food industries will be discussed in this report. Lactic acid is also widely used in textile industry, cosmetics pharmacy, tanning, and plastic industry.